Spatial analysis and socio-economic burden of road crashes in South-western Nigeria (2008)
Road traffic accidents are a major health problem in Nigeria. Death and injuries resulting from road crashes in the country have been on the increase over the years. For instance, fatality rate rose from 5.3 in 1970 to 5.8 in 2005. The purpose of the paper is to assess the pattern and socio-economic burden of road crashes on road accident victims in south-western Nigeria. The study relied on the administration of 438 questionnaires to road accident victims in both public and private hospitals in south-western Nigeria. The data were presented using descriptive statistics. Findings indicated that more than 70% of the accident victims were within the productive age group of between 15–45 years, with over 60% of them living below the poverty line. Motorcycles and buses accounted for 70% of the vehicles while about 40% of the victims were pedestrians. Each victim on average spent a minimum of US$17 per day on medical expenses and had at least one person attached to him/her throughout the period of admission. This has grave implications on the welfare of the families and the socio-economic development of the country. The paper calls for the use of preventive methods and post-crash management initiatives in order to reduce the magnitude and burden of road crashes on members of the society in south-western Nigeria.